2022
DOI: 10.3390/jcm11123318
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Threatening Ocular Adverse Events after Vaccination against Coronavirus Disease 2019

Abstract: A single-center retrospective observational case series was conducted. This case series enrolled patients who showed ophthalmic manifestations within one week after COVID-19 vaccination at Korea University Guro Hospital in Seoul, Korea, from May 2021 to January 2022. The medical records of patients who complained of ocular symptoms and showed ophthalmic adverse events within one week after COVID-19 vaccination were reviewed. Seventeen eyes from 16 patients with a mean age of 63.8 (range 33–83) years were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Ten of the 16 patients developed ocular side effects following administration of an initial vaccine dose. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 16 patients developed ocular side effects following administration of an initial vaccine dose. 7 …”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be ruled out that late-onset side effects may also occur after vaccination. While several case series suggested a causal mechanism between RVOD and COVID-19 vaccination [ 3 , 4 , 20 , 21 , 22 ], the mechanisms behind it are not understood and highly speculative. Our data, however, failed to indicate any relationship between COVID-19 vaccination and RVOD incidence.…”
Section: Discussionmentioning
confidence: 99%
“…A survey among neurologists reported a higher number of cerebral sinus and venous thromboses after SARS-CoV-2 vaccination [ 1 ], while ophthalmological case reports and small case series described numerous complications in the anterior and posterior eye segments [ 2 , 3 , 4 ]. The retinal findings cover uveitis, central serous chorioretinopathy, acute retinal necrosis, and retinal vascular alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar ocular disorders have also been observed in patients infected by the SARS-CoV-2 virus [ 24 , 25 , 26 ]. Recently, Choi and colleagues reported vision-threatening ocular adverse events in sixteen patients following SARS-CoV-2 vaccination [ 27 ]. Among these patients, the authors reported four cases of angle-closure glaucoma following the ChAdOx1 nCoV-19 vaccine and attributed it to the inflammation of the ciliary body due to vaccine-associated uveitis.…”
Section: Discussionmentioning
confidence: 99%